Psychosocial Climate and Its Relationship to Mental Distraction among Some Students of the Faculties of Physical Education and Sports Sciences - Maryam Abdul alameer Rashid; Sahira Razzaq Kazem (Institute of Medico-legal Publications Pvt Ltd, 2021)
The needs of students are many and varied in the diversity of their physical and social formation, and thepsychosocial climate, which is one of the important and influential psychological processes in the nature ofthe university atmosphere, which has an effect and relationship with mental distraction from the intellectualside, and therefore it is necessary to identify this relationship, explain it and find appropriate solutions to it,and that the rise the behavior and feeling of students should be characterized by positive energy, in additionto the morale based on the desire and the struggle to excel in the situations of university life that will resultin a certain type of distinguished activity characterized by effectiveness and perseverance.